A dictionary of psychology - Colman, Andrew M. (New York : Oxford University Press, 2001)
Contains over 10,500 alphabetically arranged entries that provide definitions and discussions of words and terms related to psychology, including psychoanalysis, psychiatry, neuroanatomy, and statistics.
Includes bibliographical references (p. [841]-844).
Choice.
Library Journal Starred.
Notable/Best Books (A.L.A.).
Adult
Keywords: Psychology -- Dictionaries; Psychology -- Dictionaries